Influence of Outer Shell Thicknes on LC Resonance and FMR in CoFeSiB/CoNi Microwires. Issue 1 (24th March 2021) - Tian, Bin; Li, Xi; Lei, Qian; Ju, Jianping
Abstract: The magnetic properties of biphase microwires which consists of CoFeSiB soft magnetic core, Pyrex glass coating and Co90Ni10 hard magnetic shell is introduced here. From the resistance spectra of GCM/CoNi (CC), two peaks are found on the resistance spectra in which one of the peaks can be considered to be caused by LC resonance depend on two main capacitors: one is the capacitor due to the interaction between the outer shell and soft core, another capacitor dues to the under action of the connector and outer shell. Obviously, the other peak is from the action of the FMR of soft magnetic core. After the welding type changed, the core and the shell were welded to the connector (CS) separately, from the differences of the resistance spectra of this welding type with the resistance spectra of GCM/CoNi (CC), the peak caused by LC resonance disappeared for the capacitance of these capacitors changed. At the same time, the capacitance of the capacitors is mainly depended on the thickness of pyrex and is independent of the outer shell thickness. These statically magneto coupled biphase systems have great potential as main sensing elements in the development of sensor devices.